Perancangan Robot Laba-Laba Pendeteksi Api Berbasis Mikrokontroller ATMEGA32 - Salahuddin Salahuddin; Widdha Mellyssa; Azman Azman (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2018)
Spider robot is controlled using ATMega32 microcontroller and programmed using C language on CV AVR Software. This robot is designed to help people in the fire fighting in the fire accident. This robot has 3 ultrasonic PING sensors that are placed on the front, right and left as a distance detector to regulate the movement of the robot and a flame detector sensor that is placed on the front as a fire detector. Robot also has 2 work modes that are manual mode and automatic mode. Manual mode is a mode where the movement of the robot is ordered to use the remote bluetooth with 7 meters of maximum distance, while the automatic mode is the mode where the movement of the robot fully using PING ultrasonic sensors. From the results of fire detection testing, the robot is able to detect the presence of fire less than 20 cm, in that position the robot will stop and turn on the fan automatically. Furthermore, from the results of robot movement testing, the robot detects the presence of obstacle as far as 20 cm, in that position the robot will stop and it will read the ultrasonic sensor PING on the right and left to decide the next movement.